Adolescent ovarian thecoma presenting as progressive hyperandrogenism: case report and review of the literature. (1st September 2020) - Gaspari, Laura; Paris, Françoise; Taourel, Patrice; Soyer-Gobillard, Marie-Odile; Kalfa, Nicolas; Sultan, Charles
Abstract: Hyperandrogenism is frequent and under investigated in adolescent girls. A 15-year-6-month-old French girl presented with oligomenorrhea and slowly progressing virilization 2 years post-menarche. Medical history revealed prenatal pesticide exposure through maternal professional activity and recurrent premature thelarche. Severe hirsutism, mild facial acne and clitoromegaly were noted. Serum androgens (testosterone: 94 ng/dL, 4-androstenedione: 8.23 ng/mL) were high and non-classic 21-hydroxylase deficiency was excluded. Pelvic ultrasonography showed a left ovarian mass, confirmed by computed tomography scan. Tumor markers were negative. Laparoscopic surgery was performed. The pathological diagnosis was benign luteinized thecoma. Postoperatively, the menstrual cycle and serum androgens became normal and hirsutism slowly improved. Hyperandrogenism 2 years after menarche should be systematically investigated, even if slowly progressive, since it may be a symptom of a rare virilizing ovarian tumor, like thecoma.